MA-XRF for the Characterisation of the Painting Materials and Technique of the Entombment of Christ by Rogier van der Weyden - Anna Mazzinghi; Chiara Ruberto; Lisa Castelli; Caroline Czelusniak; Lorenzo Giuntini; Pier Andrea Mandò; Francesco Taccetti (Applied Sciences, 2021)
At present, macro X-ray fluorescence (MA-XRF) is one of the most essential analytical methods exploited by heritage science. By providing spatial distribution elemental maps, not only does it allow for material characterisation but also to understand, or at least to have a likely idea of, the production techniques of an analysed object. INFN-CHNet, the Cultural Heritage Network of the Italian National Institute of Nuclear Physics, designed and developed a MA-XRF scanner aiming to be a lightweight, easy to transport piece of equipment for use in in situ measurements. In this study, the INFN-CHNet MA-XRF scanner was employed for the analysis of a painting by the Flemish artist Rogier van der Weyden. The painting belongs to the collection of the Uffizi gallery in Florence and was analysed during conservation treatments at the Opificio delle Pietre Dure, one of the main conservation centres in Italy. The research aims were to characterise the materials employed by the artist and to possibly understand his painting technique. Although MA-XRF alone cannot provide a comprehensive characterisation, it nonetheless proved to be an invaluable tool for providing an initial overview or hypothesis of the painting materials and techniques used.